2016
DOI: 10.3233/ch-152025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypoxia on intra-ocular, mean arterial, retinal venous and ocular perfusion pressures

Abstract: As hypoxia increases with higher altitude, arterial oxygen saturation and ocular perfusion pressure decreased, retinal venous pressure increased, intra-ocular pressure remains stable and mean arterial pressure was elevated only at 6000 m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
1
19
0
2
Order By: Relevance
“…This indicated that the haemorrhages were due to a hypoxia-induced breakdown of the barrier rather than to mechanical ruptures of a retinal vessel [206]. RVP was increased in diabetic retinopathy [316] and in high-mountain disease [244]. RVP was, as expected, increased in eyes with RVO.…”
Section: Retinal Venous Pressurementioning
confidence: 82%
See 1 more Smart Citation
“…This indicated that the haemorrhages were due to a hypoxia-induced breakdown of the barrier rather than to mechanical ruptures of a retinal vessel [206]. RVP was increased in diabetic retinopathy [316] and in high-mountain disease [244]. RVP was, as expected, increased in eyes with RVO.…”
Section: Retinal Venous Pressurementioning
confidence: 82%
“…Another patient told us that she became unconscious during a balloon ride. PVD subjects have an increased sensitivity to hypoxia, as it occurs due to low air pressure at high altitudes [244]. One NTG patient experienced a sudden onset of a scotoma during skiing, and three patients became unconscious when jumping into the cold water of the sea.…”
Section: The Patients Are Our Teachers: Clinical Symptoms Of Pvdmentioning
confidence: 99%
“…In addition, circulating ET-1 diffuses particularly around the ONH as fenestrated capillaries of the choroid enable diffusion bypassing the blood–retina barrier 20. Increased levels of ET-1 also raise retinal venous pressure as has been documented to occur during high-altitude hypoxia 21. This in turn increases the transmural pressure in the capillaries of the ONH and may therefore contribute to the formation of ODE.…”
Section: Discussionmentioning
confidence: 93%
“…Auch bei dieser venösen Konstriktion spielen lokale Hormone, insbesondere Endothelin, eine entscheidende Rolle [34]. Dies erklärt dann auch: a) warum der Venendruck in großer Höhe ansteigt [35], b) warum bei einem retinalen Venenverschluss auch der Venendruck auf der kontralateralen, klinisch nicht befallenen Seite erhöht ist [36] und c) warum der retinale Venendruck durch Kalziumantagonisten [37] und Endothelinblocker beeinflusst werden kann [38]. Menschen mit FS haben auch häufiger aktivierte retinale Astrozyten [39].…”
unclassified